MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR GEOGRAFI POKOK BAHASAN LINGKUNGAN HIDUP MELALUI MODEL PEMBELAJARAN TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) PADA SISWA KELAS XI IPS 3 DI SMAN 3 BARABAI TAHUN PELAJARAN 2013/2014 - Isnawati Isnawati (JURNAL SOCIUS, 2013)
This study background come from condition of geography lesson at SMAN 3 Barabai especially, at XI IPS 3 class show students result lesson is not yet reach minimum achievement value that is decided by school namely 70. The research is used action research method. Purpose of this research namely: for knowing activity and students result study with using STAD lesson model can increase.This research is action class research that is done with 2 cycles. Data collecting technique that is used teacher learning implementation. Result of cycle I research states from 37 present students learning process activity 40,16%, unactive 59,84%. Cycle II from present students learning process activity 76,54%, unactive 23,46% while result study from cycle I average get 54,73 while value at cycle II average 87,30. So, after learning with STAD model happen increase of result study. Keywords: Activity, Result Study, Geography, Students Team Achievement Division (STAD) Model.